Integrating Eco-Theological Values into Islamic Religious Education in Adiwiyata Schools - ainul muttaqin, muhammad; Sulaeman (LPPM Universitas Ibn Khaldun, Bogor, 2026)
The global environmental crisis demands educational interventions capable of fostering ecological awareness and sustainable behavior. This study aims to analyze the integration of eco-theological values into Islamic Religious Education at SMPN 11 Makassar, an Adiwiyata (eco-friendly) school. A qualitative case study approach was employed, involving interviews, classroom observations, and document analysis with teachers, students, and school administrators. The findings show that Islamic Education teachers integrate eco-theological values by linking Qur’anic verses with environmental issues, applying project-based learning, and modeling environmentally responsible behavior. These values are also embedded in key subjects such as aqidah, fiqh, and akhlak, and are reinforced by school policies and multi-stakeholder collaboration. The main challenges, students’ inconsistent behavior outside school and limited facilities, are addressed through partnerships and participatory programs. In conclusion, the eco-theological approach in Islamic Religious Education offers a contextual, values-based model for sustainability education that can be replicated in other school settings.